Pseudocyesis and Its Related Psychiatric Conditions: An In-Depth Analysis - Harry, Nkechinyere Mary; Folorunsho, Ibrahim; Anona, Kenechukwu; Okafor, Nnenna; Anugwom, Gibson O. (Disease and Health Research: New Insights Vol. 4, 2024)
Background: Pseudocyesis (or pseudocyesis vera) also known as “phantom pregnancy” was previously described according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) as a false belief of being pregnant that is associated with objective signs and reported symptoms of pregnancy. Depression has also been strongly reported to play a major role in the development of pseudocyesis. The exact etiology and management of this rare disorder are not known but certain factors have been associated with this including the presence of certain psychiatric conditions. Objective: This study aims to provide a better understanding of the factors associated with pseudocyesis including psychiatric disorders and available treatment modalities. Materials and Methods: This review article was done on the available literature reporting any psychiatric disorders and psychological factors in patients with pseudocyesis, the epidemiology, etiology, and methods of treatment in humans only. Available articles published from 1970 to January 2021 were included. Using the following keywords- “pseudocyesis, false pregnancy, psychiatric disorders, schizophrenia, phantom pregnancy”, relevant articles from Google Scholar, PubMed, ScienceDirect, and Web of Science were searched and reviewed. Our initial search yielded 871 articles, out of which 14 were deemed fully eligible. Results: According to our review, it has been found that various social and cultural factors such as strong cultural views on the need for childbearing as a prerequisite for womanhood, and loss of a child have led to the manifestation of this condition. The etiology of pseudocyesis is associated with various psychological and endocrine disturbances sometimes mediated by psychosomatic disorders. The treatment of pseudocyesis depends on the underlying associated conditions. In most case reports examined in this review, a multidimensional approach including psychotherapy; pharmacotherapy like antidepressants and antipsychotics; hormonal therapy such as replacement therapy, has been suggested as a promising therapeutic option. Conclusion: Pseudocyesis could be associated with psychiatric conditions such as major depression, schizophrenia, bipolar disorder, hypomania, and post-traumatic stress disorder. The treatment options may vary depending on the existence of co-morbidities in each patient. Adopting a multidisciplinary strategy that includes gynecologists, psychologists, and psychiatrists is critical in providing comprehensive care to this group of patients.